POLA PENGGUNAAN BAHASA INDONESIA DALAM PRAKTIK KOMUNIKASI FORMAL DAN NON FORMAL DI KALANGAN PELAJAR ASING DI SEKOLAH DASAR INTERNASIONAL: KAJIAN FONOLOGI - Putri, Willa (J-KIP (Jurnal Keguruan dan Ilmu Pendidikan), 2025)
This study aims to identify the patterns of Indonesian phonology use in formal and informal communication among foreign students at Al Wildan Islamic International School, Tangerang. The research employs a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The findings indicate that in formal communication, foreign students face difficulties in distinguishing between long and short vowels as well as the pronunciation of consonants, influenced by their mother tongue. In informal communication, they are more flexible and tend to adjust their accent and intonation based on their mother tongue habits, although phonological errors still occur. The international school environment and intensive social interactions play a significant role in shaping their phonological patterns. The implications of this study suggest that a deeper focus on phonology in teaching and the use of technology can help foreign students overcome pronunciation challenges in Indonesian.